Evaluating the Efficacy of a Social Media-Based Intervention (Warna-Warni Waktu) to Improve Body Image Among Young Indonesian Women: Parallel Randomized Controlled Trial - Kirsty M Garbett; Sharon Haywood; Nadia Craddock; Caterina Gentili; Kholisah Nasution; L Ayu Saraswati; Bernie Endyarni Medise; Paul White; Phillippa C Diedrichs; Heidi Williamson (JMIR Publications, 2023)
BackgroundBody dissatisfaction is a global issue, particularly among adolescent girls and young women. Effective body image interventions exist but face barriers to scaling up, particularly in lower- and middle-income countries, such as Indonesia, where a need exists. ObjectiveWe aimed to evaluate the acceptability and efficacy of Warna-Warni Waktu, a social media-based, fictional 6-episode video series with self-guided web-based activities for improving body image among young Indonesian adolescent girls and young women. We hypothesized that Warna-Warni Waktu would increase trait body satisfaction and mood and decrease internalization of appearance ideals and skin shade dissatisfaction relative to the waitlist control condition. We also anticipated improvements in state body satisfaction and mood immediately following each video. MethodsWe conducted a web-based, 2-arm randomized controlled trial among 2000 adolescent girls and young women, aged 15 to 19 years, recruited via telephone by an Indonesian research agency. Block randomization (1:1 allocation) was performed. Participants and researchers were not concealed from the randomized arm. Participants completed self-report assessments of trait body satisfaction (primary outcome) and the internalization of appearance ideals, mood, and skin shade dissatisfaction at baseline (before randomization), time 2 (1 day after the intervention [T2]), and time 3 (1 month after the intervention [T3]). Participants also completed state body satisfaction and mood measures immediately before and after each video. Data were evaluated using linear mixed models with an intent-to-treat analysis. Intervention adherence was tracked. Acceptability data were collected. ResultsThere were 1847 participants. Relative to the control condition (n=923), the intervention group (n=924) showed reduced internalization of appearance ideals at T2 (F1,1758=40.56, P<.001, partial η2=0.022) and T3 (F1,1782=54.03, P<.001, partial η2=0.03) and reduced skin shade dissatisfaction at T2 (F1,1744=8.05, P=.005, partial η2=0.005). Trait body satisfaction improvements occurred in the intervention group at T3 (F1, 1781=9.02, P=.005, partial η2=0.005), which was completely mediated by the internalization change scores between baseline and T2 (indirect effect: β=.03, 95% CI 0.017-0.041; direct effect: β=.03, P=.13), consistent with the Tripartite Influence Model of body dissatisfaction. Trait mood showed no significant effects. Dependent sample t tests (2-tailed) found each video improved state body satisfaction and mood. Cumulative analyses found significant and progressive improvements in pre- and poststate body satisfaction and mood. Intervention adherence was good; participants watched an average of 5.2 (SD 1.66) videos. Acceptability scores were high for understandability, enjoyment, age appropriateness, usefulness, and likelihood to recommend. ConclusionsWarna-Warni Waktu is an effective eHealth intervention to reduce body dissatisfaction among Indonesian adolescent girls and young women. Although the effects were small, Warna-Warni Waktu is a scalable, cost-effective alternative to more intense interventions. Initially, dissemination through paid social media advertising will reach thousands of young Indonesian women. Trial RegistrationClinicalTrials.gov NCT05383807, https://clinicaltrials.gov/ct2/show/NCT05383807 ; ISRCTN Registry ISRCTN35483207, https://www.isrctn.com/ISRCTN35483207 International Registered Report Identifier (IRRID)RR2-10.2196/33596